Pre-service Teacher Experience in Designing Lesson Using TPACK-21 CL in Teaching Reading for High School Students - Erika Novia Wardani; Nur Arifah Drajati; Ellisa Indriyani Putri Handayani (Universitas Islam Negeri (UIN) Mataram, 2020)
This study looked into the experiences of a pre-service teacher in designing a lesson using Technological Pedagogical Content Knowledge for 21st Century Learning framework. The pre-service teacher integrated the use of technology for the teaching learning process because it was to support the students to achieve the 21st skills, especially in reading. This study drew on the narrative inquiry methods to present the finding. The pre-service teacher designed the lesson followed by a reflection. This long scientific endeavor leads the preservice teacher to consider to develop technological pedagogical content knowledge (TPACK) skills to enable herself to become a professional teacher. The finding showed that though the pre-service teacher was finally able todesign the lesson and implement it in the classroom, she needs further discussion with the lecturers and the tutor teacher. The development skills from the experience is important for a teacher to be able to design meaningful learning for the students.